PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA DI INDUSTRI PERBANKAN INDONESIA - Wahyono, R. Erdianto Setyo (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2012)
This study aims to examine the effect of corporate governance on earnings managementpractices in the banking industry that are listed in the Indonesia Stock Exchange (ISX). CorporateGovernance Mechanisms used in this study is the internal mechanism. The population used in thisstudy is a banking company public limited company and the national private banking companies listedon the Indonesia Stock Exchange (ISX) in 2008-2010. Research data obtained from ISX andIndonesian Capital Market Directory (ICMD) where there are 31 companies listed on the StockExchange of banking during the period 2008-2010. Sample selection is done by purposive samplingmethod. Of the sampling method, collected 66 observations from 24 companies that went publicbanking / 3 years. By using simple regression analysis as a method of research, the results showed thatthe mechanism of corporate governance have an insignificant effect on earnings management inbanking companies go public are detected by using a specific model of accrual of Beaver and Engel(1996). The results of these studies indicate that the mechanism of corporate governance by thebanking company is not effective in reducing earnings management practices. Therefore, based on theresults of this study concluded that corporate governance mechanisms do not work effectively inimproving the performance of the banking company.Keywords: Corporate Governance, Internal Mechanisms, Earnings Management